Biomaterials modulate interleukin-8 and other inflammatory proteins during reepithelialization in cutaneous partial-thickness wounds in pigs. - Kleinbeck KR; Faucher LD; Kao WJ (Wound Repair & Regeneration)
Acute and chronic cutaneous wounds remain a clinical challenge that require a mechanistic understanding to advance treatment options. For example, the role of inflammatory mediators during wound healing is not completely understood. Biomimetic materials, such as an in situ photopolymerizable semi-interpenetrating network (sIPN) derived from extracellular matrix components, show great potential in improving healing through the delivery of therapeutic agents and the function as a temporary tissue scaffold. In this study, we characterized the temporal profile of porcine cutaneous partial-thickness wound healing in response to Xeroform™ and sIPN treatment via histological and inflammatory protein analyses in epidermal, remodeling dermal, and dermal regions. Generally, interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-10, IL-12p70, interferon-γ, and tumor necrosis factor-α, but not IL-8, were expressed in the epidermis and remodeling dermis in a time course that followed the progression of epidermal maturation in response to both treatments. Differences in cellularity and protein expression were observed between treatments in a time- and region-dependent manner. In particular, the healing response to sIPN exemplified a potentially key relationship between IL-8 expression and reepithelialization. These results provide insights into the expression of inflammatory mediators and the time course of cutaneous healing and the capacity for biomaterials to further modulate this relationship.